BSCI-19. Therapeutic intervention of lung-, breast-, and melanoma-brain metastasis. (9th August 2021) - Kieliszek, Agata; Bassey-Archibong, Blessing; Venugopal, Chitra; Singh, Sheila
Abstract: Background: The incidence of brain metastases (BM) is tenfold higher than that of primary brain tumours. BM predominantly originate from primary lung, breast, and melanoma tumours with a 90% mortality rate within one year of diagnosis, posing a large unmet clinical need to identify novel therapies against BM. Methods: Using a large in-house biobank of patient-derived BM cell lines, the Singh Lab has generated murine orthotopic patient-derived xenograft models of BM and captured a "premetastatic" population of BM cells that have just seeded the brains of mice before forming clinically detectable tumours: a cell population that is impossible to detect in human patients but represents a therapeutic window wherein metastasizing cells can be targeted and eradicated before establishing clinically detectable tumours. Results: RNA sequencing of pre-metastatic BM cells from all three primary tumour models with subsequent Connectivity Map analysis identified a lead compound that exhibits selective anti-BM activity in vitro . Preliminary in vivo work has shown that this lead compound reduces the tumor burden of treated mice compared to vehicle control while providing a significant survival advantage. Ongoing mechanistic investigations aim to delineate the protein target of this compound in the context of the observed selective anti-BM phenotype. Conclusion: Therapeutic targeting of premetastatic BM cells could prevent the formation of BM and dramatically improve the prognosis of at-risk cancer patients.